Description and Causes of Indonesian Health Workers' Anxiety During the COVID-19 Pandemic: A Mixed-Method Study - Mayang Phuspa, Sisca; Cahyantari, Umi; Anas, Hikmawani (Universitas Airlangga, 2023)
Introduction: The findings of a systematic review indicate that only a quantitative or qualitative approach was used in studies about the anxiety of health professionals during the COVID-19 pandemic. Research that aims to examine the level of anxiety experienced by Indonesian health workers during the COVID-19 pandemic, the signs and their causes will fill the scientific gap. Methods: A sequential explanatory design was used in this study. In the quantitative phase, the COVID-19 Anxiety Scale instrument was used to perform a survey on 731 healthcare workers, which was then descriptively examined. To further support its findings, 30 informants were involved to in-depth interviews, and qualitative content analysis was performed. Results: According to the poll, 15% of healthcare workers reported having high anxiety, 61% had moderate, 19% had low, and 5% had no anxiety at all. According to a qualitative content analysis, the signs of anxiety included overthinking, psychosomatic complaints, and worry about exposed to and transmit the virus at work. This is a result of managerial issues with managing pandemic, social changes, adjustments in interpersonal connection patterns, an unfriendly society, a large number of health workers who suffer with COVID-19, as well as personal variables. Conclusion: Preventive action for future health crisis situations is to improve systemic physical and non-physical preparedness in healthcare institutions. Psychosocial training programs such as cognitive coping and stress adaptation need to be carried out to improve the mental health condition of health workers so they don't ‘collapse' when dealing crisis situations.